Competitive method-based electrochemiluminescent assay with protein–nucleotide conversion for ratio detection to efficiently monitor the drug resistance of cancer cells. Issue 12 (16th August 2016) - Liang, Wen-Bin; Yang, Ming-Zhen; Zhuo, Ying; Zheng, Ying-Ning; Xiong, Cheng-Yi; Chai, Ya-Qin; Yuan, Ruo
Abstract : A competitive method-based electrochemiluminescent (ECL) assay with a single ECL indicator was proposed to efficiently estimate the concentration ratio of two proteins. Abstract : A simple and highly-efficient approach to monitor the expression of P-glycoprotein (P-gp) in cells was urgently needed to demonstrate the drug resistance of cancer cells. Herein, a competitive method-based electrochemiluminescent (ECL) assay with a single ECL indicator was proposed for the first time to efficiently estimate the concentration ratio of two proteins. By converting the different proteins to partially coincident nucleotide sequences via a sandwich type immunoassay on magnetic beads, the concentration ratio related ECL signals could be obtained via competitive nucleotide hybridization on an electrode surface. This method could thoroughly overcome the limitations of simultaneous ECL assays via multiple ECL indicators with inevitable cross reactions. At the same time, rolling circle amplification was employed to improve the detection performances, especially the detection limit and sensitivity. With P-gp and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as a model, the proposed ECL assay was successfully employed to monitor the drug resistance of cancer cells. Compared with conventional technologies, improved sensitivity and accuracy were achieved with a correlation coefficient of 0.9928 and a detection limit of 0.52%. Success in the establishment of the competitive method-based ECL assay offered an efficient strategy to demonstrate the concentration ratio of two proteins and a potential approach for detecting other proteins and nucleotide sequences, revealing a new avenue for ultrasensitive biomolecule diagnostics, especially in cell function research.